ТНЕ EFFECT OF SOIL DROUGHT ON HETEROGENEITY OF THE VARIETAL POPULATION OF WHEAT AND BARLEY - L. V. Osipova; I. A. Bykovskaya (Труды по прикладной ботанике, генетике и селекции, 2018)
In vegetative experiments with summer grain wheat and barley, heterogeneity of varieties in their resistance to an increasing soil drought has been revealed. It is established that the degree of expression of heterogeneity in varietal populations depends on the conditions of mineral nutrition and the duration of a stress.